Video Conference Rental Business Application Design At Pt. Alfa Copies Android-Based Virtual Technology - Nabil, Nabil; Mohammad Arif, Sutan; Zikriah, Zikriah (Journal of Renewable Engineering, 2024)
The purpose of this research is to determine the process of managing device rental data, tenant profiles, tenant transactions, device rental dates, payments, tenant data reports, product and price reports, sales transaction reports, bill payment reports at PT. Alfa Cipta Virtual Technology. The method used to process this activity is a qualitative method (System Life Cycle (SDLC)), namely to design, build, maintain and develop a system. After the author designs, builds and develops a device rental system, finally the author can draw the conclusion that management The device rental business becomes more dynamic and simpler so that it can improve sales and admin sales performance. Making sales transaction reports and tenant data reports is much faster because management can be accessed via an application on a smartphone.